A Nation-Wide Assessment of Empowerment Among States' Personal Protective Order Statutes. Issue 9 (May 2021) - Richards, Tara N.; Gover, Angela R.; Tudor, Alison
The Personal Protective Order (PPO) and the PPO process may provide an opportunity to shift power dynamics from the state/abuser to the victim—a process otherwise known as "victim empowerment." Using a previously established empowerment framework, the Empowerment Process Model, 2017 PPO statutes for all U.S. states and the District of Columbia ( n = 51) were examined in regard to 23 statutory elements conceptualized to facilitate the process of victim empowerment for initmate partner violence (IPV) victims. Findings demonstrated that there is little consistency across PPO statutes in regard to empowerment facilitators (8.0-18.5, M = 13.5, SD = 2.3). Three elements were found to be consistently empowering by most states: the use of gender-neutral language, inclusion of same-sex couple violence, and adherence to full faith and credit provision of Violence Against Women Act (VAWA). Future research should examine which statutory elements are associated with the greatest increases in victim empowerment, and model PPO language should be developed. Furthermore, in general, PPO research findings must be discussed within the confines of state statutes and limited generalizability across states.